Unraveling the Catha edulis Extract Effects on the Cellular and Molecular Signaling in SKOV3 Cells - Abou-Elhamd, Alaa Sayed; Kalamegam, Gauthaman; Ahmed, Farid; Assidi, Mourad; Alrefaei, Abdulmajeed Fahad; Pushparaj, Peter Natesan; Abu-Elmagd, Muhammad (Frontiers in Pharmacology, 2021)
Khat (Catha edulis Forsk) is an evergreen flowering shrub used as a stimulant in many regions worldwide, including East Africa, Arabian Peninsula, Europe, and the USA. Chewing of khat leaves induces excitement and euphoria primarily attributed to two main constituents; cathinone and cathine. A considerable number of in vivo and in vitro studies reported side effects to both embryos and adults including teratogenicity, oral cancer and ulcers, high blood pressure, and myocardial infarction. Thus far, little attention has been paid to the effects of khat on the molecular signaling of ovarian cancer. In this study, we aimed to evaluate the effects of khat extract on SKOV3, a human ovarian adenocarcinoma cell line, by in vitro assays, qRT-PCR, immunostaining, and in silico analysis. Khat induced several cellular defects including reduced cell size, damage to the cell membrane, and programmed cell death. At high concentrations, khat extract affected the cell metabolic activity, cell cycle and cellular proliferation. RT-qPCR analysis showed an increase in the expression of the apoptotic marker BAX, the tumor suppressor p53, and the inflammatory cytokine IL-6. Immunostaining analysis showed downregulation of β-catenin, E-cadherin, and Ki-67 expression and upregulation of FZD8 and SPRY2 expression suggesting that Wnt and FGF signaling were implicated. In silico analysis using SwissTargetPrediction, showed that khat constituents cathine and cathinone bind to family A G-protein-coupled receptors, cause many neurological diseases and disorders such as Alzheimer's, schizophrenia, depression, and anxiety, as well as induce many ovarian cancer-related diseases. In silico analysis identified several signaling pathways that are potentially affected by cathine and cathinone including CREB, Wnt, FGF, IL-6, ERK/MAPK, endometrial cancer, and cell cycle. Upstream regulators of cathine and cathinone were found to potentially target several molecules including Interleukin-8, MMP2, PLAU, and microRNAs.